Barriers Perceived by Teachers Regarding the Use of Distance Education Technologies for Adult Higher Education - Liang, Jia; Compan, Pongpan (Science, Technology, and Social Sciences Procedia, 2021)
The paper aimed to analyze the barriers perceived by teachers regarding the use of distance education for adult higher education and to suggest the solution to improve distance education for adult higher education. The research used Rogers’s innovation diffusion theory as a conceptual framework. The article mainly extracts 10 factors that refer to Nelson and Thompson (2005) as follow; 1) administrative structure, 2) organization change, 3) technical expertise, support, and infrastructure, 4) social interaction and program quality, 5) faculty compensation and time, 6) treat of technology, 7) legal issues, 8) evaluation effective, 9) assess, and 10) student support services. The population comes from the teachers who attend the project of adult correspondence education informatization of the author’s Unit-Beijing Open Distance Education Center Co., Ltd. Beijing University of Chemical Technology, North China University of Technology, Jinzhou Medical University, and the above 3 universities may be available to adults in the 2021 - 2022 semester. There are 250 teachers who teach correspondence education. According to the Krejcie and Morgan sample survey, the sample size is 162 teachers. The basic information includes gender, age, highest degree, major, working years, online teaching experience, teacher subject area, online teaching training. This research found that the teachers agree that the most barrier to distance education technology was the student-support services, evaluation effectiveness, and faculty compensation and time. And the treat of technology was neutral. The suggestion was to develop the network course, especially in the late innovation of the critical position, to promote resource sharing and knowledge sharing.